Sterilization procedures and Plant Preservative Mixture on in vitro establishment of Miscanthus sinensis Andersson - Ledo, Ana da Silva; Jenderek, Maria; Harrison, Melanie; Manter, Daniel; Amaral, Adriane Leite do (Plant Cell Culture & Micropropagation - ISSN 1808-9909, 2019)
Information about the establishment phase of Miscanthus sinensis as sterile procedure to avoid the contamination were few reported. The aim of this study was to evaluate different immersion sterilization procedures with and without the biocide, Plant Preserve Mixture™ (PPM™) on in vitro contamination of two Miscanthus genotypes. The plant material, canes from PI 668371 and PI 668375 accessions come from adult plants cultivated in the germplasm bank of USDA-ARS, Griffin, Georgia. Apical meristems were submitted to an immersion sterilization procedures (70% isopropyl alcohol and 1.5, 5.0 or 8.25% NaOCl for different time periods, followed by rinsing three times with autoclaved distilled water. After that, the explants were inoculated on MS basal medium in the presence or absence of 1 mL L-1 PPM™. The experimental design was fully randomized in a 2 x 5 x 2 factorial scheme (genotypes x sterilization process x PPM™) with five repetitions per treatment and five apical meristems per experimental unit. The highest level of bacterial contamination (100%) and lowest explant survival (0%) were recorded in medium without PPM™. For fungal contamination, the biocide was effective only in reducing contamination for PI 668375 due to its higher potential for fungal contamination. For both percentage of fungal and bacterial contamination, the PPM™ biocide can be an efficient agent to prevent contamination in vitro Miscanthus sp. cultures. Aseptic treatments not showed differences for percentage of bacterial and fungal contaminations and percentage of explant survival. Index terms: Micropropagation; in vitro contamination; Saccharum complex.